Pandangan Gereja Terhadap Budaya Tionghoa Altar Leluhur Meja Abu - Adam Glen; Agung Dian Rengganis (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2023)
One of valuable asset of the nation is various caltural since all we know that Indonesia has rich variaty culture widely spreaded in the nation, from Sabang to Marauke. The country of Indonesia has enormous cultural capital, has the potential to function as a source of accelerating national development more quickly.A qualitative method used in this type of reseach and included checking incident. It is a technique that combines qualitative and descriptive analysis and is used to conduct this kind of research. Findings are presented in descriptive narrative, and the authors emphasize the natural and holistic focus and multi-method research.Family can take an important role in developing their childrent's socializing skill by helping the children to understand how to respect the tradition of Ash Table, and also introducing the kids the value of religion and culture that related to their ritual.Moreover, family has a good chance to take a part as a model for others by maintaining the consistency this routine excercise to practice. This practice has the ability to lead the family to be solid and an excellent reminder of their background of ancestors and spiritual that they share to one each other.